2017
DOI: 10.1155/2017/9017078
|View full text |Cite
|
Sign up to set email alerts
|

3D Evaluation of Maxillary Sinus Using Computed Tomography: A Sexual Dimorphic Study

Abstract: Purpose. Gender determination is considered to be an important step in the reconstruction of the biological profile in forensic medicine. Maxillary sinus can be used for identification of sex when other methods are indecisive. Computed tomography (CT) provides an excellent method for examining maxillary sinuses. Hence the aim of the study was to determine the accuracy of gender determination using maxillary sinus with CT. Materials and Methods. CT images were used to measure the mediolateral, superoinferior, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 12 publications
3
22
0
4
Order By: Relevance
“…On the other hand, our results In contrast with another study that concluded The group of female revealed greater values were statistically significant for left MS width where left side MS width can be used to identify sex (6) .Also another study stated that The left MS width was the differentiation parameter (10) . Another study Concluded that comparison maxillary sinus volume between left and right sides were not statistically significant (11) .in addition to another study reported that The right MS has been reported to be greater than the left MS in both sexes (4) . Since this agreement with study that evaluated age-correlated changes in bone architecture.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…On the other hand, our results In contrast with another study that concluded The group of female revealed greater values were statistically significant for left MS width where left side MS width can be used to identify sex (6) .Also another study stated that The left MS width was the differentiation parameter (10) . Another study Concluded that comparison maxillary sinus volume between left and right sides were not statistically significant (11) .in addition to another study reported that The right MS has been reported to be greater than the left MS in both sexes (4) . Since this agreement with study that evaluated age-correlated changes in bone architecture.…”
Section: Discussionmentioning
confidence: 93%
“…The maxillary sinus is the greatest of paranasal sinuses. The sinus starts to grow at 10 weeks of embryonic life and has an opening in the middle nasal meatus of the nasal cavity (4) . At birth it begins as a pea size and continues to grow after eruption of deciduous teeth and grows again with eruption permanent teeth and with the third molars complete eruption, the sinus pneumatization ends (4) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 In view of that, there are a number of studies stating the importance of maxillary sinuses in forensic medicine, especially for gender determination, where the dimensions of sinuses between males and females are compared by means of various imaging methods. [5][6][7][8][9][10][11][12][13][14] The results of most of these studies suggested the utility of the maxillary sinuses in gender determination. Almost all these studies reported that the sinus measurement values (dimensions and volume) are larger in males than in females and they correlated this fact with the differences in the overall stature of males and females.…”
Section: Introductionmentioning
confidence: 99%